Identifying key barriers in cationic polymer gene delivery to human T cells. (11th January 2019) - Olden, Brynn R.; Cheng, Emmeline; Cheng, Yilong; Pun, Suzie H.
Abstract : Decreased uptake of polyplexes and an increased intracellular pH contribute to poor gene delivery to human T cells via cationic polymers. Abstract : T cells have emerged as a therapeutically-relevant target for ex vivo gene delivery and editing. However, most commercially available reagents cannot transfect T cells and designing cationic polymers for non-viral gene delivery to T cells has resulted in moderate success. Here, we assess various barriers to successful gene transfer in the Jurkat human T cell line and primary human T cells. Using two polymers previously developed by our group, we show that uptake is one barrier to gene delivery in primary human T cells but is not predictive of successful gene delivery. We then probe intracellular pathways for barriers to gene transfer including endosomal acidification, autophagy, and immune sensing pathways. We find that endosomal acidification is slower and not as robust in human T cells compared to the model HeLa human cell line commonly used to evaluate cationic polymers for gene delivery. These studies inform the future design of cationic polymers for non-viral gene delivery to T cells, specifically, to rely on alternative endosomal release mechanisms rather than on pH-triggered release.